Synoptic climatology of fog in selected locations of southern Poland (1966–2015) - Łupikasza, Ewa; Niedźwiedź, Tadeusz (Bulletin of Geography. Physical Geography Series, 2016)
Abstract. This paper investigates fog frequency in southern Poland in relation to various relief (concave and convex) and atmospheric circulation types. It also discusses long-term variability in the annual and seasonal number of days with fog. Daily information on fog occurrence was taken from three high quality synoptic stations representing various landforms: Kraków-Balice (bottom of the hollow), Katowice-Muchowiec (Silesian Upland) and Bielsko-Aleksandrowice (summit of Carpathian Foothill). In the central part of southern Poland during the last 50 years (1966-2015) fog occurred on average during 53-67 days a year. The annual number of foggy days in Kraków (67 days) located in a structural basin was by 14-15 days higher than in Bielsko (53 days) situated in the Silesian Foothill. In annual course high fog occurrence (above 6 days per month) was observed from September to January with maximum in Kraków (10 days in October). The monthly minimum of fog occurrence in all stations fell on July (2 days). In summer and spring the highest probability of fog occurrence was found at days with anticyclonic types and air advection from the northeastern (Na, NEa) and eastern (Ea, SEa) sectors. In autumn the high probability was also found for the anticyclonic types with advection of air mass from the eastern and southern sectors. In the Carpathian Foothill (Bielsko) the probability of fog occurrence in summer and winter was significantly enhanced only for the cyclonic types with air advection from the eastern sector (NEc, Ec, SEc) and nonadvective types Cc (cyclone center) and Bc (cyclonic trough). Fluctuations dominated in the long-term course of fog frequency. The only significant trend was found in Kraków on annual scale and in summer when fog frequency was little.